A tunable multi-resonance 2D V-groove metasurface - Zhengqing Qi; Yipin Chen; Tianjing Zhao; Peng Chen; Huizhen Yang (AIP Advances)
Based on the electromagnetic enhancement mechanism, surface-enhanced Raman scattering (SERS) substrates with multi-resonance enhancement can achieve a higher enhancement factor (EF) by matching the resonance frequencies to both the excitation and Raman scattering frequencies. In this paper, we propose a theoretical design for a tunable multi-resonance 2D V-groove plasmonic substrate, constructed from an Ag–SiO2–Ag metasurface that incorporates established silicon processing technology. The excellent 2D multi-resonance substrate expands conventional electromagnetic “hotspot” to a “hot line,” thereby providing a larger and more robust coupling regime for SERS detection. The inclined plane serves as a “trap” and ensures the target molecules fall into the “hot line.” Theoretically, the EF of SERS can reach up to 5.12 × 1011, surpassing that of traditional nanoparticle antennas. The proposed 2D plasmonic substrate serves as an exceptional platform for multi-resonance SERS applications.